Approach to Determine the Density‐of‐States Effective Mass with Carrier Concentration‐Dependent Seebeck Coefficient. (9th June 2022) - Lee, Kyu Hyoung; Kim, Sang‐il; Lim, Jong‐Chan; Cho, Jung Young; Yang, Heesun; Kim, Hyun‐Sik
Abstract: Band engineering is an effective strategy to improve the electronic transport properties of semiconductors. In thermoelectric materials research, density‐of‐states effective mass is an undoubted key factor in verifying the band engineering effect and establishing a strategy for enhancing thermoelectric performance. However, estimation of the effective mass is demanding or inaccurate depending on the methods taken. A simple equation is proposed, valid for all degeneracy: Log10 ( md * T /300) = (2/3) Log10 ( n ) − (2/3) [20.3 − (0.00508 × | S |) + (1.58 × 0.967 | S | )] that utilizes experimentally determined Seebeck coefficient ( S ) and carrier concentration ( n ) to determine the effective mass ( md *) at a temperature ( T ). This straightforward equation, which gives an accurate analysis of the band modulation in terms of md *, is indispensable in designing thermoelectric materials of maximized performance. Abstract : The density‐of‐states (DOS) effective mass of thermoelectric materials can be estimated accurately with the single parabolic band model. However due to complex Fermi integral calculations involved, an equation that is valid in degenerate materials is instead utilized erroneously. This work proposes another simple, universal, and accurate equation that can be used for any degeneracy to determine the DOS effective mass.